Briefing: An experimental procedure to assess the erosional behaviour of cohesionless soils. Issue 4 (20th August 2019) - Haouzi, Fatima Zahra; Esnault-Filet, Annette; Courcelles, Benoit
Abstract : Selective erosion of fine particles from granular soils can affect the draining properties of hydraulic structures with time, and it is important to identify unstable soils and characterise their hydraulic and erosional behaviour. To this end, this study focuses on the design and set-up of a new laboratory device for testing the suffusion and piping phenomenon occurring in an internally unstable cohesionless material. The proposed procedure offers the possibility of quantifying the hydraulic gradient at which erosion starts and evaluates the mass of fine particles washed out of the sample under controlled hydraulic conditions. The quantity of eroded particles, the exit water flow rate and the hydraulic gradient distribution along the flow paths are also measured during the process. The procedure was tested on an erosive soil under saturated conditions and under unconfined seepage, allowing the assessment of the hydraulic behaviour of this internally unstable material.